Solvent used in extraction process of agarwood: a systematic review - Zakaria, F.; A. Talip, Balkis; M.Kahar, E.E.; Muhammad, N.; Abdullah, N.; Basri, H. (Rynnye Lyan Resources, 2020)
The method of extraction of Agarwood is usually dependent on the purpose of the extract. This systematic review aims to look at the number of studies that use different types of solvents in the process of extraction. There are 3 types of solvents commonly used in the extraction of agarwood essential oils namely methanol, ethanol and water. Each solvent produces different extracts in terms of quantity and quality of the final product. However, there is controversy over the use of solvents as it may cause a cytotoxic effect on the user. Another common type of solvent is water. Although water is a cheap solvent and relatively safe, aqueous extracts have more impurities that make isolating the desired compound difficult. After the extraction process, the crude extract was fractionated into the desired compounds and this technique is widely applied, especially in the whole process of extraction of the agarwood. In conclusion, extraction solvents have certain advantages and disadvantages, and this is one of the reasons why this extraction method depends on the purpose of using the final product such as agarwood essential oil.